Evaluation of the effect of zinc supplementation on total serum bilirubin (TSB) in neonatal hyperbilirubinemia - Mohammed Farrag Abdelmonem Mohammed; Manar Aref Eldesouky; Nahed Abdelwahab Mohamed; Reem Nabil Said (Cairo : Mohammed Farrag Abdelmonem Mohammed, 2019)
Background: Zinc is one of the essential elements in neonatal growth, protein synthesis and regulation of inhibitory and stimulatory synapses of the brain. Zinc lower the bilirubin levels by inhibition of the normal enterohepatic circulation of unconjugated bilirubin (UCB). Objectives: to evaluate the effect of oral zinc therapy on total serum bilirubin in neonatal hyperbilirubinemia. Materials and Methods: In our randomized clinical trial, a total of 80 full term healthy neonate ages 2-7 days with physiological jaundice whom required phototherapy were enrolled in the study performed, Cairo University (EL Monira). the neonates included in the study were randomly assigned to one of two groups : Group (1): 40 neonates received oral zinc, in a dose of 10 mg once daily from 2-5 days in combination with phototherapy. Group (2): 40 neonates received phototherapy without oral zinc. Serum zinc was measured with serum bilirubin during admission and on discharge for both groups. The total serum bilirubin level was measured at the beginning, 12 hours, 24 hours for both groups. Results: Administration of oral zinc decreases serum UCB levels and decrease the duration of phototherapy in neonatal jaundice. Conclusions: Zinc supplementation decrease serum total bilirubin level and decrease duration of phototherapy
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Hyperbilirubinemia; Phototherapy; Zinc